Study of Serum Iron, Calcium and Phosphorus Level in Lactating Women Compared with Non Lactating Women in Bangladesh - Azad, Afroza; Rahman, Md Rezwaur; Ruba, Rubayea Afrin; Biswas, Prithwy Shankar; Tuli, Jesmin Zahan (Delta Medical College Journal, 2025)
Background: Lactation encompasses the process of milk production and secretion by mammary glands. It significantly influences the levels of serum iron, calcium, and phosphorus, thereby elevating the risks of osteoporosis, malnutrition, and other maternal complications. Objective: the aim of this study was to evaluate serum iron, calcium and phosphorus status in lactating women in Bangladesh. Materials and method: This case control study was carried out in the department of Biochemistry, Mymensingh Medical Collcge, Mymensingh, with the collaboration of the department of Gynaecology and Obstetrics, Mymensingh Medical College Hospital, Mymensingh, during the period of July 2016 to June 2017. A total of 60 apparently healthy lactating women were selected as case and 60 apparently healthy non-lactating women were selected as control. Serum iron, calcium and phosphorus levels were measured for both groups. Statistical analyses of the results were obtained by using Statistical Packages for Social Sciences (SPSS-22) software. Results: The mean ± SD serum calcium levels were estimated to be 7.74±0.67 mg/dL in lactating women and 8.75±0.78 mg/dL in non-lactating women respectively, and the difference was statistically significant (p<0.05). But the serum iron and serum phosphorus were not significantly changed between two groups. Conclusion: There is no significant difference in serum iron and phosphorus levels between lactating and non-lactating women but significantly decreased serum calcium level is observed in lactating women. Delta Med Col J. Jan 2022;10(1): 25-30